Dry Deposition Methods Based on Turbulence Kinetic Energy: 1. Evaluation of Various Resistances and Sensitivity Studies Using a Single‐Point Model. Issue 22 (25th November 2022) - Alapaty, Kiran; Cheng, Bin; Bash, Jesse; Munger, J. William; Walker, John T.; Arunachalam, Saravanan
Abstract: Different functions are used to account for turbulence strength in the atmospheric boundary layer for different stability regimes. These functions are one of the sources for differences among different atmospheric models' predictions and associated biases. Also, turbulence strength is underrepresented in some of the resistance formulations. To address these issues with dry deposition, firstly we take advantage of three‐dimensional (3‐D) turbulence information in estimating resistances by proposing and validating a 3‐D turbulence velocity scale that is relevant for different stability regimes of boundary layer. Secondly, we hypothesize and validate that friction velocity measured by 3‐D sonic anemometer can be effectively replaced by the new turbulence velocity scale multiplied by the von Karman constant. Finally, we (a) present a set of resistance formulations for ozone (O3 ) based on the 3‐D turbulence velocity scale; (b) intercompare estimations of such resistances with those obtained using existing formulations; and, (c) evaluate simulated O3 fluxes using a single‐point dry deposition model against long‐term observations of O3 fluxes at the Harvard Forest (MA) site. Results indicate that the new resistance formulations work very well in simulating surface latent heat and O3 fluxes when compared to respective existing formulations and measurements at a decadal time scale. Findings from this research may help to improve the capability of dry deposition schemes for better estimation of dry deposition fluxes and create opportunities for the development of a community dry deposition model for use in regional/global air quality models. Plain Language Summary: Chaotic air motions control the amount of pollutant transfer to the surface during dry conditions, which can impact ecosystems, and is a helpful process that can reduce human exposure to air pollutants. Existing pollutant transfer equations use adjustment methods to account for chaotic air motions for different dry conditions. These methods can be sources of errors in estimating pollutant transfer. To avoid using such methods, we propose and evaluate a new velocity parameter derived from using chaotic air energy, which is estimated using other air parameters. Then, we validate the new velocity parameter using sophisticated instrument measurements for chaotic motions. Further, we assume and prove that a constant fraction of that new velocity parameter can be used to avoid adjustment methods and accurately represent strength of chaotic air motions. Finally, we use that new velocity parameter in developing new equations that estimate ozone transfer via various routes to the surface. We used a computer based tool to validate new equations using decadal measurements of ozone fluidities at the Harvard Forest site. Results indicate that our new equations work very well in estimating pollutant transfer. This research has the potential to help manifest a community science package for use in mathematical models. Key Points: Turbulence velocity scale is introduced to represent 3‐D turbulence strength in the estimation of dry deposition Proven measured friction velocity can be replaced by von Karman constant and turbulence velocity scale product to avoid stability functions New formulations based on turbulence velocity scale simulated realistic surface latent heat and ozone deposition fluxes at decadal time scales